2020
DOI: 10.20899/jpna.6.1.5-21
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Relationship Between Emotion Management and Social Capital: An Analysis of Federal Employees

Abstract: Emotion management describes the ability of an employee to regulate the outward manifestation of emotions during personal interactions. Prior studies examining emotions in organizations have often emphasized the production of emotional labor during service delivery transactions with clients. Such a focus has overlooked the emotion management that takes place between employees. Using ordinary least- squares (OLS) regression, this study analyzes the 2016 Merit Principles Survey of federal employees to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
(97 reference statements)
0
7
0
1
Order By: Relevance
“…While scholars have often described emotional labor as a requirement of employees that helps the organization achieve its goals (Hochshild 1983), additional research suggests that meeting the emotional requirements of a job can provide employees with individual benefits by helping them develop colleague relationships that are associated with social capital (Humphrey 2020). Statements from this sample provide additional support to research in this area.…”
Section: Resultsmentioning
confidence: 99%
“…While scholars have often described emotional labor as a requirement of employees that helps the organization achieve its goals (Hochshild 1983), additional research suggests that meeting the emotional requirements of a job can provide employees with individual benefits by helping them develop colleague relationships that are associated with social capital (Humphrey 2020). Statements from this sample provide additional support to research in this area.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research suggests that employees willing to invest in relationships with their colleagues through emotion management activities can enhance their social capital (Humphrey, 2020). However, there is also evidence that people of color tend to have less social capital compared with White employees (James, 2000).…”
Section: Employee To Employee: Relationships and Social Capitalmentioning
confidence: 99%
“…However, there is also evidence that people of color tend to have less social capital compared with White employees (James, 2000). Even when participating in emotion management, which is often associated with the development of social capital, they still perceive themselves as having little social capital compared with their White counterparts (Humphrey, 2020). Additional studies have found similar findings and suggest that although employees of color and White employees report similar levels of providing emotional support to coworkers, employees of color are less likely to feel supported by coworkers and report having fewer social ties (Sloan et al, 2013).…”
Section: Employee To Employee: Relationships and Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Örneğin çocuk refah alanında çalışan bir sosyal hizmet uzmanı para kazanmak için değil, işinin bir parçası olduğu için duygularını yönetmektedir. Niven, Totterdell, ve Holman (2009) duygusal emek yerine duygu yönetimi kavramının kullanılmasının daha uygun olduğunu belirmektedirler; çünkü kişinin duygularını kontrol etmesi iş için gerekli bir görev olarak tanımlanmamakta ve iş sözleşmesinde belirtilmemektedir (Humphrey, 2020). Bu çalışmada duygu yönetimi, hangi ortamda meydana geldiklerine bakılmaksızın, bireylerin içinde bulundukları durumlarla kendi duygularını uyumlu hale getirerek içsel bir bütünleşme sürecinin sağlanmasına ilişkin gösterilen çabayı ifade edecek şekilde kullanılmaktadır.…”
Section: Introductionunclassified